PSVIII-30 Gastrointestinal nematode resistance in variable stress-responding sheep. (7th December 2018) - Borkowski, E; Karrow, N; Mallard, B; Menzies, P; Avula, J; Lillie, B; Peregrine, A
Abstract: Stress is known to contribute to variation in cell-mediated (CMIR) and antibody-mediated (AbMIR) immune responses. Our group previously demonstrated that variation in the ovine cortisol response to immune stress challenge with Escherichia coli lipopolysaccharide (LPS) was associated with immunity; high (HSR) and low (LSR) stress-responsive sheep exhibited heightened CMIR and attenuated AbMIR compared to middle (MSR) stress responders. However, the association of this stress response phenotype with resistance to gastrointestinal nematodes (GIN) has not been investigated, which was the focus of this study. Two hundred GIN-naïve Rideau lambs were LPS challenged, and the peak cortisol response was used to select 15 HSR lambs and 15 MSR lambs from the population. These lambs were then naturally challenged with GINs while co-grazing with a commercial flock in Ontario known to carry GINs for five months in 2016. Infection was confirmed by monitoring fecal egg counts (FEC) every 6–8 weeks, and at the end of the grazing season, the HSR and MSR lambs (n=30) were euthanized to assess GIN burden (abomasum and small intestine). Two-sample T-tests were performed to compare FEC and GIN burden between the HSR and MSR sheep. No significant differences were found in FEC at any of the sampling time points, or in the end-of-season GIN burden. It is possible that the parasite challenge was insufficient to reveal differences in GIN resistance between the groups, since pasture burden was unusually low due to a record drought during the 2016 grazing season. Further investigation into other health phenotypes that may influence GIN resistance, such as high immune response, is warranted.